Analysis of the Influence of User Interface (UI) and User Experience (UX) on Big Data Application on Administrative Dashboard Function Interest on Portal News - Firmansyah, Muhamad Dody; Saaya, Zurina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The activities of the National Police are closely related to the community, therefore social media is an obligation for the National Police to involve themselves with the community, especially in the digital era which continues to open opportunities and improve technology. This research aims to determine the dashboard interface factors that can influence its function. This model is TAM and questionnaires will be distributed to staff admin and the data will be analyzed using Multiple Linear Regression, after analysis, interviews will be conducted with several selected people. The research results show that usefulness and ease of use have a huge influence on attitude towards using and this is represented in the real world by 56%. Ease of use and attitude towards using have a huge impact on actual system use and this is represented in the real world by 76%. The research concluded that usability and ease of use are important to pay attention to in order to increase user satisfaction and interest. Ease of use and user interest must be considered to increase application use. Still, usability should not be given too much attention because usability is more focused on user satisfaction and interest.